Novel Ricin Subunit Antigens with Enhanced Capacity to Elicit Toxin-Neutralizing Antibody Responses in Mice - Wahome, Newton (J Pharm Sci, 2016)
RiVax is a candidate ricin toxin subunit vaccine antigen that has proven to be safe in human Phase I clinical trials. In this study we introduced double and triple cavity-filling point mutations into the RiVax antigen with the expectation that stability enhancing modifications would have a beneficial effect on overall immunogenicity of the recombinant proteins. We demonstrate that two RiVax triple mutant derivatives, RB (V81L/C171L/V204I) and RC (V81I/C171L/V204I), when adsorbed to aluminum salts adjuvant and tested in a mouse prime-boost-boost regimen were 5 to 10-fold more effective than RiVax at eliciting toxin-neutralizing serum IgG antibody (TNA) titers. Increased TNA values and seroconversion rates were evident at different antigen dosages and within seven days following the first booster. Quantitative stability/flexibility relationships (QSFR) analysis revealed that the RB and RC mutations affect rigidification of regions spanning residues 98 to 103, which constitutes a known immunodominant neutralizing B cell epitope. A more detailed understanding of the immunogenic nature of RB and RC may provide insight into the fundamental relationship between local protein stability and antibody reactivity.